2020
DOI: 10.1016/j.ijso.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the postoperative analgesic-associated side effects and clinical parameters following partial mastectomy

Abstract: Background: Lumpectomy (partial mastectomy) is associated with a severe postoperative pain that can lead to chronic pain. The use of analgesia is common for this pain management, however, can impose a number of side effects. Objective: The aim of this study is to evaluate side effects following postoperative analgesia use and the impact of clinical factors among partial mastectomy patients. Method: This cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…With the increased use of X-rays and gamma rays for various therapeutic and diagnostic purposes, potential health hazards have risen concerns 8 . The effect of ionizing radiation on increasing the risk of cancer as well as its other destructive effects on other organs of the body has been proven 9 – 11 . The main source of ionizing radiations for irradiators and other personnel is scattered or secondary ionizing radiations left over from the primary ionizing radiations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…With the increased use of X-rays and gamma rays for various therapeutic and diagnostic purposes, potential health hazards have risen concerns 8 . The effect of ionizing radiation on increasing the risk of cancer as well as its other destructive effects on other organs of the body has been proven 9 – 11 . The main source of ionizing radiations for irradiators and other personnel is scattered or secondary ionizing radiations left over from the primary ionizing radiations 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Katsuda et al ( 13 ) theorize that nerve terminals are heated by electric current in electrosurgical incisions of spine surgeries, and patients experience less discomfort during the recovery phase ( 13 ). A study found that using electrocautery for tissue dissection increases postoperative pain, necrosis, and severe tissue injury ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, opioid use is associated with dose-dependent complications such as respiratory depression, nausea, vomiting, urinary retention, pruritus, drowsiness, or postoperative ileus [ 13 , 14 ]. Therefore, it seems reasonable to use compounds that can intensify the analgesic effects of narcotics and thus create better analgesic effects with less opioid use [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%